Comparison of the VO2 response to 800-m, 1 500-m and 3 000-m track running events - Duffield, R.; Bishop, D.; Dawson, B. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The present study examined the VO2 response to middle-distance track running events of 800 m, 1 500 m and 3 000 m and investigated the relationship between the speed of the V.O2 response ((1) and subsequent race performance. Methods: Trained 3 000-m (n=8), 1 500-m (n=10) and 800-m (n=8) male track athletes performed a laboratory GXT plus a run at 14 km·h-1 and multiple race time trials. For each subject, a bi-exponential model fit from 20 s was used to categorise the O2 response for the best performed track run and also the treadmill run at 14 km·h-1. Results: Faster (1 values were noted the shorter the track event, with values of 14, 18.5 and 20.8 s for 800-, 1 500- and 3 000-m events, respectively. ANOVA results revealed that differences in (1 were significant (P<0.05) for the 800- and 3 000-m, but not for the 800- and 1 500-m (P=0.06) or 1 500- and 3 000-m events (P=0.15). Only 1 500-m race performance was significantly correlated to race (1 (r=0.71). Values for (1 at an absolute velocity treadmill run (14 km·h-1) did not differ significantly between different events and were not correlated to race performance for any event. From pooled data for all three events, significant correlations (P<0.01) were noted between t1 and the speed over the first 800-m (r=-0.54 to -0.68). Conclusions: There was a trend for faster (1values the shorter the track event. The significant correlation between t1 and initial starting velocity suggests this may be attributed to the faster starting velocity of the shorter track events, rather than any differences between athletes per se.